Microwave-assisted solvothermal synthesis of hierarchical TiO2 microspheres for efficient electro-field-assisted-photocatalytic removal of tributyltin in tannery wastewater. (July 2017) - Zhao, Yang; Huang, Zhiding; Chang, Wenkai; Wei, Chao; Feng, Xugen; Ma, Lin; Qi, Xiaoxia; Li, Zenghe
Abstract: Organotin compounds have been widely used in recent decades, however, the residential tributyltin (TBT) in environment has potential harmful effects on human health due to the disruption of endocrine system even at trace level. Herein, this work reports on an effective electro-field-assisted-photocatalytic technique for removal of TBT by applying an electric field to photocatalysis of as-prepared hierarchical TiO2 microspheres. The synthesis of catalytic materials is based on a self-assembly process induced by microwave-assisted solvothermal reaction. Hierarchical TiO2 microspheres consisting of nanowires can be obtained in short time with this facile method and possess high surface area and superior optical properties. As the catalyst, it was found that the reaction rate constant of electro-field-assisted-photocatalytic removal (0.0488 min −1 ) of TBT exhibited almost a 9 fold improvement as compared to that of photocatalysis (0.0052 min −1 ). The proposed mechanism of electro-field-assisted-photocatalytic removal of TBT was verified by using 117 Sn-enriched TBT spike solution as an isotopic tracer. In addition, varying impacts from some key reaction conditions, such as voltage of potential, pH value and the presence of Cr and formaldehyde were also discussed. The overall satisfactory TBT removal performance of the proposed electro-field-assisted-photocatalysis procedure with hierarchical TiO2 microspheres, which was validated using actual tannery wastewater samples from three different kinds of tanning procedures. These attributes suggest that this electro-field-assisted-photocatalysis may have broad applications for the treatment of tannery wastewater. Highlights: Hierarchical TiO2 were prepared by a rapid microwave-assisted solvothermal process. Hierarchical TiO2 spheres with nanowire building units possess high surface area. Electro-field-assisted-photocatalysis showed 9 times the activity of photocatalysis. 117 Sn-enriched spike solution was used to verify the degradation process of TBT. Actual tannery wastewater can be treated by electro-field-assisted-photocatalysis.